Influence of Blackberry Plants on the Aroma Profile of Vitis vinifera L. cv. Pinot Noir - Tomasi, D.; Alessandrini, M.; Barcarolo, R.; Gaiotti, F. (South African Journal of Enology and Viticulture, 2017)
V. vinifera cv. Pinot noir vines were grown in pots together with blackberry plants and the effect of this association on the grape aroma was assessed. Preliminary data showed that vines that cohabited with blackberry had a different aroma profile compared to vine grown alone. The association with blackberry increased the concentration of 30 out 74 free aroma compounds and of 24 out 95 bound ones. No aroma compound was identified exclusively in the treated grapes.